Rates of Fe(II)-Oxidation and Solubility of Bacteriogenic Iron Oxides. Issue 3 (15th March 2016) - Ferris, F. Grant; Enright, Allison M.L.; Fortin, Danielle; Clark, Ian D.
ABSTRACT: The oxidation of Fe(II) at circumneutral pH by natural bacterial consortia capable of oxidizing Fe(II) in flocculent mats of bacteriogenic iron oxides (BIOS) was investigated in a series of microcosm experiments under constant pH and pO2 conditions. The oxidation of Fe(II) was faster in the presence BIOS compared to chemical oxidation in solution with pseudo–first-order rate constants ranging from 0.036 to 0.248 min −1 for BIOS compared to 0.004 min −1 for the chemical control. The Fe(II)-oxidation rates exhibited a kinetic dependency on BIOS concentrations, measured in terms of a pseudo–second-order rate constant at 0.066 Lg −1 min −1 . From the asymptotic decline in Fe(total) in the microcosms, apparent rate constants for HFO dissolution (zero-order values 0.001 to 0.046 mgL −1 min −1 ) and precipitation (second-order values 0.007 to .297 min −1 ) were obtained from the BIOS and control microcosms, which yield an apparent equilibrium BIOS solubility of 0.157 mgL −1 (i.e., 2.8 μM). These results reflect the complex interplay of Fe(II) oxidation reactions associated with BIOS including homogenous chemical oxidation in solution, chemical oxidation on HFO surfaces, and bacterially mediated oxidation. Furthermore, BIOS precipitated in response to Fe(II) oxidation exhibit a greater apparent solubility than more stable varieties of HFO. The implication is that the competitive advantage of Fe(II)-oxidizing bacteria over autocatalytic surface chemical Fe(II) oxidation on HFO might be enhanced by a reduction in the total amount of BIOS that is precipitated.